Perencanaan Kapasitas Produksi Menggunakan Metode Rough Cut Capacity Planning pada Home Industry Roti NK - Rianti Indah Lestari; Sukriyah Buwarda; A.Dian Sry Rezki Natsir; Riskawati (Jurnal Serambi Engineering, 2024)
Home industry is a type of SME (Small and Medium Enterprise) that can promote community self-reliance and boost Indonesia's economic growth. NK Bread Home Industry produces various types of bread, including white bread, gembul bread and sweet bread. This home-based industry uses a make-to-order production system, with production levels based on orders. In order to anticipate fluctuations in demand, this industry also maintains stocks. The main problem for this cottage industry is the lack of accuracy in inventory planning due to the lack of demand forecasting. As a result, production is based on experience. In addition, production output is not maximised due to the lack of production capacity planning. This research aims to plan production capacity using the RCCP (Rough-Cut Capacity Planning) method with the BOLA (Bill of Labor Approach). The results obtained show that the required capacity is 1878.50 units, which is greater than the available capacity of 1417.26 units per period. In order to solve this problem, recommendations are made, such as the need to increase the number of workers, the number of machines, the adjustment of the production rate and the use of subcontracting. With these suggestions, it is expected that the production house will be able to maximise capacity, leading to an increase in production output.